MEMPELAJARI VIABILITAS ENKAPSULASI SEL PROBIOTIK (LACTOBACILLUS PLANTARUM DAN STREPTOCOCCUS THERMOPHILUS) PADA ES KRIM: ( Study Viability Encapsulation of Probiotic Cells (Lactobacillus plantarum and Streptococcus thermophilus) on Ice Cream) - Maryati Bilang; Mulyati Tahir; Darmayanti Haedar (jurnal1, 2018)
Encapsulation is one of the methods of protecting bacteria in unfavorable environmental conditions such as processing, storage and digestion. The aim of this research was to investigate the encapsulation effect of Lactobacillus plantarum and Streptococcus thermopillus on ice cream during frozen storage (-28oC). The study also was to investigate its resistance to stomach acid condition (pH 2.0) and bile salt (0.5%), and its effect on organoleptic and overrun ice cream. Encapsulation was performed using an emulsion technique with sodium alginate as a coating. Bacterial resistance was seen from the total amount of Lactic Acid Bacteria during storage. The results showed that there was no significant difference (P>0.05) on the organoleptic ice cream Lactic Acid Bacterial were encapsulated and not during storage. The value of overrun ice cream free lactic acid bacteria is greater than the ice cream in encapsulated lactic acid bacteria.The results showed that there was significant difference (P<0.05) on the viability Lactic Acid Bacteria were encapsulated and not during storage. Lactobacillus plantarum and Streptococcus thermopillus without encapsulation has decreased as much 1.25CFU Log g-1(12%)and 2.56CFU Log g-1 (25%). While Lactobacillus plantarum and Streptococcus thermopillus with encapsulated orespectively decreased to 0.20 log CFU g-1(2%) and 1.45CFU Log g-1 (14%)after eight weeks storage. Similarly, in gastric acid conditions pH 2 and 0.5% bile salts, encapsulated Lactic Acid Bacteria have better resilience than unencapsulated Lactic Acid Bacteria.Therefore, encapsulated lactic acid bacteria have better viability to freezing temperatures, gastric acid and bile salts during frozen storage